2019
DOI: 10.1093/aobpla/plz045
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome, physiological and biochemical analyses reveal response mechanism mediated by CBF4 and ICE2 in enhancing cold stress tolerance in Gossypium thurberi

Abstract: Low temperature is one of the key environmental stresses that impair plant growth and significantly restricts the productivity and spatial distribution of crop plants. Gossypium thurberi, a wild diploid cotton species, has adapted to a wide range of temperatures and exhibits a better tolerance to chilling stress. Here, we compared phenotypes and physiochemical changes in G. thurberi under cold stress and found this species indeed showed better cold tolerance. Therefore, to understand the molecular mechanisms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
3

Relationship

5
5

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 106 publications
3
15
0
Order By: Relevance
“…the results obtained were in agreement to previous ndings which have shown that G. thurberi is more tolerant to both biotic stress condition, more so to Verticillium dahliae which is a fungal pathogen which causes Verticillium wilt, a terminal disease to various crops (Dong et al 2019). Moreover, in the study carried by Cai et al (Cai et al 2019) revealed that G. thurberi was highly tolerant to cold stress compared to G.trilobum. Furthermore, Kirungu et al (Kirungu et al 2018a) found that G. klotzschianum harbored more bene cial traits compared to G. davidsonii.…”
Section: Rt-qpcr Validation Of the Selected Genes Within The Sdr Regisupporting
confidence: 92%
“…the results obtained were in agreement to previous ndings which have shown that G. thurberi is more tolerant to both biotic stress condition, more so to Verticillium dahliae which is a fungal pathogen which causes Verticillium wilt, a terminal disease to various crops (Dong et al 2019). Moreover, in the study carried by Cai et al (Cai et al 2019) revealed that G. thurberi was highly tolerant to cold stress compared to G.trilobum. Furthermore, Kirungu et al (Kirungu et al 2018a) found that G. klotzschianum harbored more bene cial traits compared to G. davidsonii.…”
Section: Rt-qpcr Validation Of the Selected Genes Within The Sdr Regisupporting
confidence: 92%
“…The results obtained were in agreement to previous ndings which have shown that G. thurberi is more tolerant to both biotic stress conditions, more so to Verticillium dahliae which is a fungal pathogen causing Verticillium wilt, a terminal disease to various crops (Dong et al 2019). Moreover, in the study carried by Cai et al (Cai et al 2019) revealed that G. thurberi was highly tolerant to cold stress compared with G.trilobum. Furthermore, Kirungu et al (Kirungu et al 2018) found that G. klotzschianum harbored more bene cial traits compared with G. davidsonii.…”
Section: Stress Conditionssupporting
confidence: 92%
“…The results obtained were in agreement to previous findings which have shown that G. thurberi is more tolerant to both biotic stress conditions, more so to Verticillium dahliae which is a fungal pathogen causing Verticillium wilt, a terminal disease to various crops (Dong et al 2019). Moreover, Cai et al (2019) revealed that G. thurberi was highly tolerant to cold stress compared with G.trilobum. Furthermore, Kirungu et al (2018) found that G. klotzschianum harbored more beneficial traits compared with G. davidsonii.…”
Section: Rna Sequence Data Analysis Profiled Under Abiotic Stress Consupporting
confidence: 91%